Japan$1 (Bs Humanitarian Aid Toward Myanmar After the 2021 Coups Exploring Four Channels Amid the Weaponization of Assistance - Hattori, Ryuji; Khai, Tual Sawn.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open access book delves into Japan's humanitarian aid efforts in Myanmar following the military coup of February 2021. As Myanmar faces political upheaval and growing humanitarian challenges, Japan's response has been notable, yet intricate, maneuvering through obstacles created by the Myanmar military's weaponization of aid. Utilizing document analysis, semi-structured interviews, and fieldwork conducted at the Myanmar-Thailand border, this book explores four key channels through which Japan delivers humanitarian assistance: UN organizations, Myanmar-based NGOs, Thailand-based NGOs, and Bangladesh-based NGOs. Each channel is examined in detail, highlighting the strategies employed, obstacles faced, and impact of Japan$1 (Bs contributions on the ground. This study illuminates the precarious equilibrium between delivering crucial aid and addressing the political circumstances that hinder humanitarian endeavors. It also prompts important discussions about the morality of providing assistance in conflict-ridden areas and the responsibilities of donor nations in upholding their human rights. This book is ideal for academics, decision-makers, and humanitarian professionals, and not only enlightens readers about Japan's distinctive position in Myanmar, but also contributes to wider debates on international aid dynamics in politically fraught environments.s
Table of Contents -- About the Authors -- Abbreviations -- List of Tables and Figures Introduction -- Chapter 1 Humanitarian Assistance in Civil Wars and the Evaluation Criterion -- Chapter 2 Human Security in Myanmar -- Chapter 3 Navigating Aid Delivery Japan s Multifaceted Approach to Myanmar s Crisis -- Conclusion -- Appendix -- Interview -- Field Research in Thailand -- Reference.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: International relations; Peace; Economic development; Human rights; Emigration and immigration -- Government policy; Emigration and immigration; International Relations; Peace and Conflict Studies; Development Studies; Politics and Human Rights; Migration Policy; Human Migration